Recurrent hypoglycaemic seizures and suppressed ketogenesis in a child with heterozygous ABCC8 mutation: a case of delayed presentation of familial hyperinsulinemia hypoglycemia - Swaraj, S. L. Akhila; Anirudh, A. T. (International Journal of Contemporary Pediatrics, 2025)
Familial hyperinsulinemic hypoglycemia (FHH) is a rare genetic disorder characterized by inappropriate insulin secretion, resulting in persistent hypoglycemia. We report the case of a 3-year-8-month-old girl who presented with recurrent seizure-like episodes following a history of refractory neonatal hypoglycemia. Biochemical evaluation during hypoglycemic episodes revealed inappropriately normal insulin levels and significantly suppressed beta-hydroxybutyrate levels. Genetic analysis identified a heterozygous missense mutation in the ABCC8 gene. This case underscores the importance of recognizing low ketone levels during hypoglycemia as a critical diagnostic clue for hyperinsulinism. It also highlights that heterozygous ABCC8 mutations, traditionally associated with recessive inheritance, can present with clinically significant disease. Early recognition and intervention are crucial to preventing long-term neurodevelopmental impairment.